The symbiosis between Lophelia pertusa and Eunice norvegica stimulates coral calcification and worm assimilation. - Christina E Mueller; Tomas Lundälv; Jack J Middelburg; Dick van Oevelen (PLoS ONE, 2013)
We investigated the interactions between the cold-water coral Lophelia pertusa and its associated polychaete Eunice norvegica by quantifying carbon (C) and nitrogen (N) budgets of tissue assimilation, food partitioning, calcification and respiration using (13)C and (15)N enriched algae and zooplankton as food sources. During incubations both species were kept either together or in separate chambers to study the net outcome of their interaction on the above mentioned processes. The stable isotope approach also allowed us to follow metabolically derived tracer C further into the coral skeleton and therefore estimate the effect of the interaction on coral calcification. Results showed that food assimilation by the coral was not significantly elevated in presence of E. norvegica but food assimilation by the polychaete was up to 2 to 4 times higher in the presence of the coral. The corals kept assimilation constant by increasing the consumption of smaller algae particles less favored by the polychaete while the assimilation of Artemia was unaffected by the interaction. Total respiration of tracer C did not differ among incubations, although E. norvegica enhanced coral calcification up to 4 times. These results together with the reported high abundance of E. norvegica in cold-water coral reefs, indicate that the interactions between L. pertusa and E. norvegica can be of high importance for ecosystem functioning.